Favourable Outcome in Pediatric Neurosurgery for Extra Dural Hematoma in Sub Sahara Africa: Report of Parakou University Hospital in the Benin Republic - K Quenum; Oh Fatigba; Yp Houndje; C Tchegnonsi; T Alihonou; Wa Guedjo (Journal of Neurological Research And Therapy, 2020)
Introduction The extra dural hematoma is a blood collection between the cranial vault and the dura mater. It is a neurosurgical emergency whose statistical data are poorly known in the Republic of Benin. Objective The aims of this study are to assess epidemiology, therapeutic and outcome of traumatic extra dural hematomas for children admitted to the surgical department of CHUD-B/A from 2012 to 2017. Methods This was a cross-sectional, descriptive and retrospective study over a period from January 1st, 2012 to December 31st, 2017. Results One hundred and seventy-eight cases of children aged between 0-15 years were examined for brain traumatic injury. Twenty-seven 27 (15.2%) cases of extra dural hematomas were retained. The most represented age group was between 11-15 years with a frequency of 42.1%. The male sex was more represented (78.9%). Road traffic accidents were the main aetiology (57.9%). 52.6% had a mild head injury, 26.3% had a moderate head injury and 21.1% had a severe head injury. On brain scan the frequently observed location was temporo-parietal (31.6%). Acute anemia was observed in 16 children. Seventeen children were operated on. The operation involved evacuation of extra dural hematoma by cranial bone flap with suspension of the dura mater. There were no deaths. Conclusion The availability of brain CT makes the diagnosis of extra dural hematoma easier. Its management is neurosurgical with a favourable post-operative evolution in all cases in this series.
Keywords: Head injury